The ballet collaborations of Richard Strauss - Heisler, Wayne, 1970- (Eastman studies in music, 2009)
In 'The Ballet Collaborations of Richard Strauss', Heisler considers Strauss's ballet scores alongside story, mise-en-scène, and choreography, revealing Strauss's shift from a parodic conception of classical dance in the years leading up to World War I to a belated obsession with Romantic-era ballet in its aftermath. Heisler explores issues central to Strauss's relationship to modernism: his mining in 'Die Insel Kythere' (1900) of the decorative aspects of dance, suggesting a shared sensibility with fin-de-siècle Jugendstil and a critique of Romanticism; the dynamics of collective creation and Strauss's penchant for parody in relation to 'Josephslegende' (1914); his stance on interwar cultural politics through the 1923 'Ballettsoirée' and 'Schlagobers' (1924); and 'Verklungene Feste' (1941) as this composer's autumnal meditation on the conceit of music and dance as vehicles for transcendence. 'The Ballet Collaborations of Richard Strauss' is a richly interdisciplinary study that promises to nuance the popular, critical, and academic reception of this ever-popular composer. Wayne Heisler Jr. is assistant professor and Coordinator of Historical and Cultural Studies in Music at The College of New Jersey.